The DAMPAK KEMITRAAN CREATED SHARED VALUE PT. GREAT GIANT LIVESTOCK TERHADAP PENDAPATAN PETERNAK SAPI POTONG DI KELOMPOK LIMOUSIN, DESA ASTOMULYO - Aisyah Nisa'ul Fitri (Balitbangda Provinsi Lampung, 2022)
This study aims to describe the implementation of PT. Great Giant Livestock’s CSV partnership programs in the Limousin Group and determine the impact of the CSV partnership implemented by Great Giant Livestock Company on the income of beef cattle farmers in the Limousin Group. This research was conducted in April – May 2022 in the Limousin Group, Astomulyo Village, Central Lampung regency. The choice of research location was determined intentionally using purposive sampling, considering that Limousin Group is a partner group of Great Giant Livestock Company which is in ring 3 with the highest number of members still actively collaborating with the company. The technique for determining respondents was a census in the Limousin Group of as many as 60 respondents. Data was collected using interviews with questionnaire instruments and observation. The method of analysis is descriptive and uses multiple linear analyses. The descriptive analysis results obtained that the partnership's planning and implementation are in a suitable category. The numerous linear analysis results show that the partnership's performance partially affects the partnership's impact. The partnership's planning and implementation simultaneously affect the partnership's impact on the income of beef cattle farmers. Partnership planning and implementation affect revenue by 20.2%.